LEGAL PROTECTION OF MEDICAL AND HEALTH PERSONNEL IN THE IMPLEMENTATION OF COVID-19 VACCINATION - Faddly Hendarsyah (Universitas Lampung, 2022)
The COVID-19 disease outbreak in 2019 brought many impacts on human life. Many people died due to Covid-19, and countries worldwide are trying to find solutions so that the COVID-19 outbreak can be overcome. Vaccines are the best solution for now in providing prevention of the COVID-19 pandemic. The government also organizes mandatory COVID-19 vaccinations for the public to avoid this COVID-19 disease. The issuance of the approval for the COVID-19 vaccination is carried out because it is a public health emergency or Emergency Use Authorization (EUA). This research uses normative juridical research methods and empirical legal research. In general, research activities are carried out by collecting sources from reading materials such as books and laws and regulations and conducting several interviews. The results from this study show that medical and health personnel have received legal protection in implementing COVID-19 vaccination, both preventively and repressively. On the other side there are factors that have the potential to cause medical disputes are Unexpected Events after COVID-19 Vaccination, incomplete information from officers, incomplete and correct information and information from the patient regarding the patient's medical history, incorrect assessment of the state of the vaccine target, and negligence of officers. However, this can be prevented by conducting education related to AEFI, ensuring the quality and safety of vaccines and injectable vaccines according to the correct procedures, increasing officers' knowledge and ability, and doing suitable IEC for patients.